Network Security Management Audit at UUM Computer Centre - Mohamad Fadli, Zolkipli (2004)

(untitled)
An organization needs to evaluate its network security in order to measure accountability, confidentiality, integrity, authority and also its authenticity. The method that is commonly used for this purpose is by conducting an audit. Using the auditing method, this research attempts to evaluate the network security at the UUM Computer Centre. The purpose of this paper is to identify the network security deficiencies at UUM Computer Centre. Results from the network security audit will then be used to recommend solution to improve those loopholes. The selected audit method is based on the Information Protection and Security Division of University Computing Services (IP & SD UCS), from The State University of New Jersey.